Water pressure effect and influence mechanism of coal mechanical property degradation under mine water immersion conditions - Xiaohu Zhu; Zeliang Liang; Jia Tan; Yi Wang; Heng Zhang (PLoS ONE, 2025)
This study investigates the hydro-pressure effects and degradation mechanisms of coal under mine water immersion using a self-developed pressurized water soaking system. Uniaxial compression tests were conducted on water-saturated coal samples to analyze their mechanical behavior under varying water pressures. The results demonstrate that both the strength and elastic modulus of coal samples decrease with increasing immersion pressure. During loading, multiple deformation localization zones develop, and the elastic energy stored in the load-bearing structure diminishes as water pressure rises, reducing its energy storage capacity. Therefore, in the process of plastic deformation, the externally applied energy contributes more to the macroscopic and microscopic damage. When the material is immersed in high-pressure water, its failure mode will shift from tensile dominant to tensile shear composite mechanism, which not only exacerbates internal damage but also significantly accelerates the deterioration process of the fracture surface. Quantitative analysis shows that both surface porosity and probability entropy are positively correlated with immersion pressure. Furthermore, increasing water pressure enhances the pressure-driven water-coal interaction, particularly in acidic mine water environments, leading to the softening, argillization, and dissolution of hydrophilic clay minerals, thereby reducing their relative content. These findings provide theoretical insights for optimizing coal mine hydraulic technologies, enhancing gas extraction efficiency, and ensuring underground stability.